Tropical range grasses can sustain soil functions despite nutrient depletion in semiarid degraded land - Patidar, Pankaj; Sannagoudar, Manjanagouda S.; Ghosh, Avijit; Singh, Amit Kumar; Misra, Sukanya; Khandibagur, Vanitha; Ojha, Deepak; Casini, Ryan; Elansary, Hosam O.; Chandra, Amaresh (Frontiers in Sustainable Food Systems, 2023)
Soil function encompasses numerous functions and services the soil provides and can be measured using physical, chemical, and biological characteristics. In any event, research on fertility and biological activity is increasingly being stressed as indices of ecosystem services. Rangeland degradation is one of the world's most widespread land use changes, with serious consequences for soil processes and ecosystem services. The influence of uncontrolled grass cover on soil functioning in semiarid environments is little understood. In the current study, the following seven varieties of grass coverings were studied in a semiarid area of central India: Cenchrus ciliaris (CC), Megathyrsus maximus (MM), Chrysopogon fulvus (CF), Heteropogon contortus (HC), Sehima nervosum (SN), Vetiveria zizanioides (VZ), and Tri-Specific Hybrid (TSH). The carbon accumulation proficiency of TSH, MM, and HC was ~2.23, 2.17, and 2.07 times greater than fallow. The nutrient cycling capacity of grasses was ~1.1 to 1.6 times greater than that of fallow, despite the grasses' depleted macronutrients in the soil. The biological activity under MM and HC was ~1.23 and 1.67 times higher than fallow. Overall soil functionality under TSH and HC was 83 and 25% greater than MM, respectively. These soil functions augment ecosystem services like climate regulation, biomass production, nutrient recycling, water, and airflow. However, more attention should be paid to the management of inputs for greater ecosystem services from this grass cover in semiarid, degraded land.